Spermine oxidase induces DNA damage and sensitizes fusion negative rhabdomyosarcoma cells to irradiation - Perrone, Clara; Pomella, Silvia; Cassandri, Matteo; Pezzella, Michele; Giuliani, Stefano; Gasperi, Tecla; Porrazzo, Antonella; Alisi, Anna; Pastore, Anna; Codenotti, Silvia; Fanzani, Alessandro; Barillari, Giovanni; et al. (Frontiers in Cell and Developmental Biology, 2023)
Rhabdomyosarcoma (RMS) is a pediatric myogenic soft tissue sarcoma that includes fusion-positive (FP) and fusion-negative (FN) molecular subtypes. FP-RMS expresses PAX3-FOXO1 fusion protein and often shows dismal prognosis. FN-RMS shows cytogenetic abnormalities and frequently harbors RAS pathway mutations. Despite the multimodal heavy chemo and radiation therapeutic regimens, high risk metastatic/recurrent FN-RMS shows a 5-year survival less than 30% due to poor sensitivity to chemo-radiotherapy. Therefore, the identification of novel targets is needed. Polyamines (PAs) such as putrescine (PUT), spermidine (SPD) and spermine (SPM) are low-molecular-mass highly charged molecules whose intracellular levels are strictly modulated by specific enzymes. Among the latter, spermine oxidase (SMOX) regulates polyamine catabolism oxidizing SPM to SPD, which impacts cellular processes such as apoptosis and DNA damage response. Here we report that low SMOX levels are associated with a worse outcome in FN-RMS, but not in FP-RMS, patients. Consistently, SMOX expression is downregulated in FN-RMS cell lines as compared to normal myoblasts. Moreover, SMOX transcript levels are reduced FN-RMS cells differentiation, being indirectly downregulated by the muscle transcription factor MYOD. Noteworthy, forced expression of SMOX in two cell lines derived from high-risk FN-RMS: 1) reduces SPM and upregulates SPD levels; 2) induces G0/G1 cell cycle arrest followed by apoptosis; 3) impairs anchorage-independent and tumor spheroids growth; 4) inhibits cell migration; 5) increases γH2AX levels and foci formation indicative of DNA damage. In addition, forced expression of SMOX and irradiation synergize at activating ATM and DNA-PKCs, and at inducing γH2AX expression and foci formation, which suggests an enhancement in DNA damage response. Irradiated SMOX-overexpressing FN-RMS cells also show significant decrease in both colony formation capacity and spheroids growth with respect to single approaches. Thus, our results unveil a role for SMOX as inhibitor of tumorigenicity of FN-RMS cells in vitro. In conclusion, our in vitro results suggest that SMOX induction could be a potential combinatorial approach to sensitize FN-RMS to ionizing radiation and deserve further in-depth studies.